Social Dynamics and the Evolution of Disciplines. - Wong, Kekoa; Rubin, Hannah (Philosophy of Science, 2024)
We consider the long-term evolution of science and show how a "contagion of disrespect"—an increasing dismissal of research in subfields associated with marginalized groups—can arise due to the dynamics of collaboration and reputation (versus, e.g., preconceived notions of the field's worth). This has implications both for how we understand the history of science and for how we attempt to promote diverse scientific inquiry.